Cervical artery tortuosity is associated with intracranial aneurysm. Issue 5 (July 2017) - Labeyrie, Paul-Emile; Braud, Florent; Gakuba, Clément; Gaberel, Thomas; Orset, Cyrille; Goulay, Romain; Emery, Evelyne; Courthéoux, Patrick; Touzé, Emmanuel
Background: Intracranial aneurysms may be associated with an underlying arteriopathy, leading to arterial wall fragility. Arterial tortuosity is a major characteristic of some connective tissue disease. Aim: To determine whether intracranial aneurysm is associated with an underlying arteriopathy. Methods: Using a case-control design, from May 2012 to May 2013, we selected intracranial aneurysm cases and controls from consecutive patients who had conventional cerebral angiography in our center. Cases were patients with newly diagnosed intracranial aneurysm. Controls were patients who had diagnostic cerebral angiography and free of aneurysm. The prevalence of tortuosity, retrospectively assessed according to standard definitions, was compared between cases and controls and, association between tortuosity and some aneurysm characteristics was examined, in cases only. Results: About 659 arteries from 233 patients (112 cases and 121 controls) were examined. Tortuosity was found in 57 (51%) cases and 31 (26%) controls (adjusted OR = 2.71; 95%CI, 1.53–4.80). The same trend was found when looking at each tortuosity subtype (simple tortuosity, coil, kink) or at carotid or vertebral territory separately. In contrast, no association between tortuosity and rupture status, aneurysm number or neck size was found. Conclusions: Cervical artery tortuosity is significantly associated with intracranial aneurysm, although not related to main aneurysm characteristics. Our results support the presence of an underlying diffuse arteriopathy in intracranial aneurysm patients.